Sermons and Talks Volume two - White, Ellen Gould Harmon 1827-1915 (E. G, White Estate, 1994)
During the 70 years of her ministry, Ellen White was called upon to speak in just about every imaginable situation. In this volume we can read her transcribed material as she originally gave it.